2002
DOI: 10.1007/s00424-002-0886-x
|View full text |Cite
|
Sign up to set email alerts
|

Is lactate a mediator of hypoxia-induced anapyrexia?

Abstract: Hypoxia causes a regulated decrease in body core temperature ( T(c)), termed anapyrexia, which seems to be a very effective way of preventing hypoxia-associated cell damage. Since during several pathological states the supply of O(2) is a limiting factor, the clinical importance of anapyrexia is evident. However, the mechanisms involved in this response remain unclear. We tested the hypothesis that lactate, a classic companion of hypoxia, is a mediator of hypoxia-induced anapyrexia, using the inhibitor of acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…Both traits are related since hypoxia elicits an array of compensatory responses, among them is anapyrexia, the regulated drop of body temperature, which is a very efficient way to prevent cellular damage caused by hypoxia . The general importance of anapyrexia resides in the fact that it reduces the consumption of oxygen and increases the affinity of haemoglobin to oxygen (Bicego et al, 2002;Steiner et al, 2002). Variations in temperature tend to affect the entire organism (Odehnalová et al, 2008); the neonate piglets that obtained a low vitality score showed hypercapnia, results in agreement with previous work by Randall (1971) and Herpin et al (1996); whereas more recently, Groenendaal et al (2009) indicated that hypothermia affects PCO 2 diminishing this gas concentration at low temperatures.…”
Section: Vitality: Body Temperature and Blood Gasessupporting
confidence: 82%
“…Both traits are related since hypoxia elicits an array of compensatory responses, among them is anapyrexia, the regulated drop of body temperature, which is a very efficient way to prevent cellular damage caused by hypoxia . The general importance of anapyrexia resides in the fact that it reduces the consumption of oxygen and increases the affinity of haemoglobin to oxygen (Bicego et al, 2002;Steiner et al, 2002). Variations in temperature tend to affect the entire organism (Odehnalová et al, 2008); the neonate piglets that obtained a low vitality score showed hypercapnia, results in agreement with previous work by Randall (1971) and Herpin et al (1996); whereas more recently, Groenendaal et al (2009) indicated that hypothermia affects PCO 2 diminishing this gas concentration at low temperatures.…”
Section: Vitality: Body Temperature and Blood Gasessupporting
confidence: 82%
“…Nonetheless, under SMF, rats exposed during 15 days displayed an increase in lactate concentration. This increase of lactate can be the sign of hypoxia state, as suggested by several authors (Bicego et al 2002;Gargaglioni et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Although direct calorimetry is needed to fully address this issue, the observed increase in blood lactate levels during exposure to 9% O 2 supports this hypothesis. Blood lactate levels also increase in rats during acute hypoxia (7% O 2 ) (Bicego et al, 2002); interestingly, there was no correlation between blood lactate levels and T b depression in the rat, suggesting that there is no direct relationship between anaerobic heat production and T b depression in that species. These data suggest that increased thermolysis is principally responsible for the reduced T b during hypoxia in Japanese quail, and perhaps in other birds.…”
Section: Discussionmentioning
confidence: 99%